Electron Doping by Charge Transfer at LaFeO3/Sm2CuO4 Epitaxial Interfaces. (4th January 2013) - Bruno, Flavio Y.; Schmidt, Rainer; Varela, Maria; Garcia‐Barriocanal, Javier; Rivera‐Calzada, Alberto; Cuellar, Fabian A.; Leon, Carlos; Thakur, Pardeep; Cezar, Julio C.; Brookes, Nicholas B.; Garcia‐Hernandez, Mar; Dagotto, Elbio; et al.
<x xml:space="preserve">Abstract</x> Using X‐ray absorption spectroscopy and electron energy loss spectroscopy with atomic‐scale spatial resolution, experimental evidence for charge transfer at the interface between the Mott insulators Sm2CuO4 and LaFeO3 is obtained. As a consequence of the charge transfer, the Sm2CuO4 is doped with electrons and thus epitaxial Sm2CuO4/LaFeO3 heterostructures become metallic. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>